Training on the Use of School Administration System Application Smp N 2 Lebong Atas - Siska, Jumiati; Susanto , Edy; Aniarti (Universitas Dehasen Bengkulu, 2019)
This purpose of this activity are, first, provide companionship to the school administration system integrated to provide quick, effective and accurate services. Second, fix the quality management system of institutional to reach the school’s objectives. The method used are training, FGD, and Mentoring. The result show that, first, preparation Integrated School Administration System (SISDU) goes well. Obstacles encountered in the implementation of the infrastructure that SISDU is still limited and the ability of teachers to operate system needs to be improved. Second, the activities preparation of ISO-based governance system in general has been running well, but school administrators are still unfamiliar about the documents in the ISO standardize, they are already accustomed to using predefined Education Offices’ documents.